Pengaruh Pelatihan, Pengembangan Sumber Daya Manusia dan Insentif Terhadap Kinerja Pegawai di PT. Fumindo Abdi Lestari Medan - Julienda Br. Harahap; Sri Elny; Julkarnain Julkarnain (Universitas Nusantara PGRI Kediri, 2023)
The Effect of Training, Human Resource Development and Employee Incentives on Performance in PT. Abdi Fumindo Medan Lestari. The Purpose of this study was to determine the effect of Training, Human Resource Development and Incentives on Employee performance in PT. Abdi Fumindo Medan lestari. The method used in this research is using descriptive analysis techniques and multiple liner regression analysis. The collection method using secondary data. The results of processing, showing that the performance of the variable has a value of training on average 45.200 with a standard deviation of 3.188, subsequent to the development of a variable indicates that the average value of 42.685 with standard deviation of 3.419 and variable Incentive has an average value of 43.857 with standard deviation of 2.390. The result of Statistical tests simultaneously seen that value F 14.207, Ftable value obtained from the F distribution value at N=35 for Alpha= 0.05% by 4.50. This mean that the Hypothesis that if the F value is greater than the Ftable then the Hypothesis that there is a Positive and Significant effect of all Independent Variables and Dependent Variable ( Performance ) is acceptable. Determinants of test result obtained by value of R2=57.90, this figure shows that the changes in Performance due to changes in the variable of Training, Human Resource Development and Incentive for the remaining 57.9% change in the Performance variable due factors-a factor that is not mentioned in this study.